Biochemical characteristics of a mutant of the methanoarchaeon Methanothermobacter thermautotrophicus resistant to the protonophoric uncoupler TCS - Cijbonová, L; Majerník, A; Smigán, P (Folia microbiologica, 2004)
In an attempt to more closely define a protein basis of differences in ATPase and ATP synthase activities in a mutant of the methanoarchaeon Methanothermobacter thermautotrophicus resistant to the protonophoric uncoupler TCS (3,3',4',5-tetrachlorosalicylanilide), the composition of membrane associated proteins from the wild-type and mutant strains has been compared. The uncoupler-resistance in the mutant strain was not accompanied by changes in a protein size or changes in the level of subunits A, B and c (proteolipid) of the A1A0-type ATPase-synthase. On the other hand, we revealed a 670-kDa membrane-associated protein complex that is abundantly present only in the mutant strain; it is composed of at least 5 different subunits of 95, 52, 42, 29 and 22 kDa.
Keywords: archeální proteiny; Electrophoresis, Polyacrylamide Gel; Membrane Proteins; Methanobacteriaceae; elektroforéza v polyakrylamidovém gelu; antibiotická rezistence; podjednotky proteinů; molekulová hmotnost; mutace; Blotting, Western; Proton-Translocating ATPases; Archaeal Proteins; protonové ATPasy; Protein Subunits; inhibitory enzymů; membránové proteiny; salicylanilidy; Drug Resistance, Microbial; Salicylanilides; Mutation; western blotting; Enzyme Inhibitors; Molecular Weight